Representatives of the Kokan School of Coppersmithing, Glorifying the National Craft - Kasimova Nilufar Muratjon Kizi; Kasimov Barkamol Salijan o’glu (International Journal on Economics, Finance and Sustainable Development, 2022)
The art of coppersmithing is one of the ancient and national types of applied art, and the Kokan school of this art is developing in its own way. He was the son of Mulla Otaulla Muhammad Rajab, the founder of the Kokan school of coppersmithing and embroidery. After the master's death, his descendant Lutfullo Fazilov continued the Kokan school of coppersmithing and embroidery.